A base nacional comum curricular e suas implicações para o ensino da oralidade no ensino fundamental – anos finais - Ferreira Junior, Edson Gomes (Universidade Federal Rural do Semi-Árido, 2020)
The teaching of orality in Basic Education is provided for in several official documents that guide and regulate Brazilian education. Among them, we highlight the National Common Curricular Base (NCCB), recently approved and published by the Ministry of Education, a document that aims to promote a redesign of Brazilian education, reinforcing the theoretical concepts already proposed in other documents such as the National Curriculum Parameters (NCP), published at the end in the 1990s. In this context, the teaching of orality is highlighted due to its relevance to the subject's sociocommunicative development, with the school being the main responsible for developing the skills and competences necessary for the performance of the subject in a literate society that requires the user of the language the full command of orality and writing in different situations. Thus, the present documentary research, of qualitative nature and exploratory and descriptive in nature, has as main objective to analyze the skills focused on the teaching of orality at NCCB, from the oral genres, in order to carry out the mapping of these skills and the description of the categories of orality that should be taught in the classroom. Therefore, NCCB is the universe of this research. We start from the conception of language as interaction (BAKHTIN, 2007) and from school as a literacy agency that needs to prepare students for mastering the language in more formal situations. To theoretically base our research, we rely mainly on Bakhtin (2016), Bezerra (2017), Marcuschi and Dionísio (2007), Schneuwly and Dolz (2011), ForteFerreira; Noronha e Soares, (2017), Brun (2017). As for the methodology, we organized our journey in three steps: first, we delimit the universe of our research, focusing our attention on the skills that make up the learning objectives for the teaching of Portuguese Language in Elementary Education - final years. In this stage, we seek to map these skills, identifying in each of them the possibility of working on orality from the oral genres explicit in the skills. Then, we separated the skills that directed to work with the oral modality of the language, relating them to the categories of orality that should be worked on in the classroom and, finally, we describe the categories of orality that we relate to the skills through of the proposed oral genres and research by Forte- Ferreira (2014), Noronha (2018), Jacob, Diolina and Bueno (2018), bringing to the discussion important reflections about teaching these categories around working with orality in a perspective of language as interaction. To describe our methodological process, we used Gil (2002, 2008), Fonseca (2002) and Ludke and André (2014). The results show that of the total of 63 skills present in the 6th and 7th grades, only 7 are directed to work with orality. Regarding the skills targeted for 8th and 9th grade, out of 65 skills, only 7 contemplate working with the oral language. In addition, the analysis enabled the identification of the following oral categories present in the skills directed to the teaching of orality: argumentation, conversational markers, speech turns, paralinguistic, kinetic and prosodic elements. Thus, we conclude that it is necessary to understand these constituent elements of orality so that the student can achieve, in fact, the skills necessary for his performance in different communication situations, in the most diverse contexts of society
Keywords: Oralidade; Ensino; Gêneros orais; Orality; Teaching; Oral genres; MULTIDISCIPLINAR::ENSINO